I have a solution to a logic problem involving propositions that I don't undersand how a particular step was carried out.The professor called the step I'm having trouble with reverse distribution.

Prove: $(p \lor q ) \land\lnot (p \lor \lnot q)\leftrightarrow p$

$(p \lor q ) \land (p \lor \lnot q) $

$p\lor(q \land \lnot q)$ This is the step I don't understand.

$p\lor FALSE $


The second step is throwing me for a loop. What am I not seeing?


Since $\vee$ distributes over $\wedge$, you know that $A\vee(B\wedge C)$ is equivalent to $(A\vee B)\wedge(A\vee C)$. So if you have the former, you can replace it with the latter.

But, likewise, if you have the latter, you can replace it with the former. Your second line, $(p\wedge q)\vee(p\wedge\neg q)$ is of the form $(A\vee B)\wedge(A\vee C)$ (with $A=p$, $B=q$, and $C=\neg q$), so it is equivalent to $A\vee(B\wedge C)$, which is exactly the third line.

In other words: instead of using the "distributive property" as usual, you use it "in reverse". It's much like going from $5\times 3 + 5\times 7$ to $5\times(3+7)$, instead of the other way around. You can think of it as the analogue of "factoring out" instead of "distributing through".

  • 3
    $\begingroup$ Dr. Magidin I really appreciate all the answers over the last few weeks. you have been very help. Thank you. $\endgroup$ – lampShade Jan 31 '11 at 4:02

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.